Estimating Parameters and Predicting the Risk of MiscarriageInfertility, and Psychological Disorders Among Chemical Attack Survivors of Kurdistan by Using Multinomial Logistic Regression Analysis - Nazeera Sedeek Kareem Al Barznji (Zanco Journal of Humanity Sciences)
Since the Ba'ath regime took over Iraq, they oppressed the Kurdish nation in every way. In 1987, on the pretext of the Iran-Iraq war, they bombed the two cities (Sardasht and Piran shar) in East Kurdistan   After that year, 40 villages and cities in South Kurdistan were bombed include of them was Halabja on 3/16/1988. In addition to 5,000 martyrs and 10,000 wounded, most of the people of Halabja suffer from various diseases, to determine the level of risks of chemical gas to survivors suffering from miscarriage, infertility and mental disorders, this study was recorded by interviewing (500) infected people recorded in the Ministry of Martyrs and Anfal in Kurdistan.The results found that the most risk on [Abortion disease, Psychological disease (female), Infertility disease(male),  and transmission of disease], and the level (0.70-0.90) is the most affected by the chemical gases that cause Miscarriage, infertility, and Psychological diseases In this paper IBM SPSS software used for Analyzing the data.